Visual Data Mining: Digital Visual Activities In Network Society - Jokhanan Kristiyono; Maulia Jayantina Islami; Ratna Puspita Sari; Suprihatin Suprihatin (Universitas Darussalam Gontor collaboration with ISKI (Ikatan Sarjana Ilmu Komunikasi Indo, 2022)
This article describes scientific discoveries that drive the phenomenon of visual cultural communication media in networked societies. Many types of research on visual culture have focused more on visual arts and mass media. However, few have yet addressed the problem of people's digital activities in searching for visual information on the Internet ( Visual search engine as a resource for visual data mining The amount of digital information, including visual information, is increasing exponentially.This research uses a literature study method with a qualitative approach. The primary data used in this study are studies on visual culture and visual search engines published in international peer-reviewed journals. Analysis of digital behavior and visual culture in a networked society is described as a research topic in previous research results. The conclusions drawn indicate that there is still a relatively deep and broad analysis of the study of visual culture when using digital communication media. There are few research studies on visual culture and digital activities in connected communities, especially people's visual information search behavior.